2017
DOI: 10.1007/s11356-017-0623-9
|View full text |Cite
|
Sign up to set email alerts
|

The integrative effect of periphyton biofilm and tape grass (Vallisneria natans) on internal loading of shallow eutrophic lakes

Abstract: The response of periphyton biofilm and the submerged macrophyte tape grass (Vallisneria natans) to internal loading from eutrophic lake sediments were evaluated in microcosms. The sediments from the littoral zone and center of a lake were selected to carry out the microcosm experiment. To determine how the differences in the periphyton biofilm and V. natans growth alone or in combination, we measured changes in water quality, growth, and TP in the periphyton biofilm and V. natans in microcosms containing these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Comprehensively, taking in to consideration the cost performance and construction convenience, the AAP was a more favorable material, with longevity over 15 years, for the application in the ecological restoration of shallow eutrophic waters. Due to the structure of plentiful micropores between the microfibers (8.5-9.0 cm per microfiber), the periphyton is provided with adhesive surfaces of 8000 m 2 /m 3 , and results in strong adsorption and absorption.Research concerning periphyton has predominantly focused upon the purifying capacity of periphyton in bioreactors and rivers [23,24], while studies in eutrophic lakes remain rare [25,26]. Taking the periphyton biofilm as an assemblage, there is a need to understand the performance and processes involved with algal-bacterial biofilm-based wastewater treatment projects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensively, taking in to consideration the cost performance and construction convenience, the AAP was a more favorable material, with longevity over 15 years, for the application in the ecological restoration of shallow eutrophic waters. Due to the structure of plentiful micropores between the microfibers (8.5-9.0 cm per microfiber), the periphyton is provided with adhesive surfaces of 8000 m 2 /m 3 , and results in strong adsorption and absorption.Research concerning periphyton has predominantly focused upon the purifying capacity of periphyton in bioreactors and rivers [23,24], while studies in eutrophic lakes remain rare [25,26]. Taking the periphyton biofilm as an assemblage, there is a need to understand the performance and processes involved with algal-bacterial biofilm-based wastewater treatment projects.…”
mentioning
confidence: 99%
“…Research concerning periphyton has predominantly focused upon the purifying capacity of periphyton in bioreactors and rivers [23,24], while studies in eutrophic lakes remain rare [25,26]. Taking the periphyton biofilm as an assemblage, there is a need to understand the performance and processes involved with algal-bacterial biofilm-based wastewater treatment projects.…”
mentioning
confidence: 99%
“…biofilm had no significant effect on the growth of V. natans , which is similar to the conclusion that the periphyton biofilm is beneficial to the growth of V. natans . [ 64 ] However, Song et al. [ 65 ] showed that the attachment of Leptolyngbya sp.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment pH and Eh were measured in situ using a portable pH meter (PHB-4; Leici, Shanghai, China) and an Eh meter (SX712; Ruisun, Chengdu, China), respectively [9]. Organic matter (OM) content in sediments was determined based on wet combustion with K 2 Cr 2 O 7 , and measured through titration with (NH 4 ) 2 Fe(SO 4 ) 2 •6H 2 O [22].…”
Section: Sediment Physicochemical Analysismentioning
confidence: 99%
“…Submerged macrophytes are distributed extensively in freshwater environments and can be obtained relatively easily; consequently, they represent ideal natural materials for controlling internal P loading from sediments. In addition, the efficiency of submerged macrophytes in controlling internal P loading may be enhanced by integration with in situ P passivation [8,9].…”
Section: Introductionmentioning
confidence: 99%